Mercado encantado : trocas, memória e encantamento no comércio afrorreligioso do mercado municipal de Aracaju-SE - Loeser, Breno da Costa (2022)
This work proposes an analysis of the exchange of knowledge and products linked to Afroreligious practices and beliefs within the complex of markets in the center of Aracaju-SE. When considering markets as the central scenario of this work, it was necessary to approach the exchange relations of those who transact Afro-Brazilian objects, inputs, and knowledge, in order to understand how utilitarian and non-utilitarian exchanges are manifested in this space, seeking to if we also understand how sacred commerce is constituted and how it contributes to local memory. We sought, mainly, to understand the circularity of Afroreligious exchanges and knowledge in the complex of municipal markets in Aracaju-SE, analyzing them from an epistemological point of view that approaches the Afro-religious narratives, having as reference the categories of myth, rite, exchanges, sacred, memory and enchantment for the delimitation of the concept of enchanted market. It was interested to understand how the system of total benefits of Mauss (1950) and manifests in the market of Aracaju/SE, to investigate which knowledge is transacted, the sellers, the types of afroreligious products that are commercialized, the impacts of religious festivities for the sellers and discover how the relationship between the house of Ashe and the market is built. Methodologically, this research begins with a bibliographic survey that addresses concepts relevant to the project concomitant with the field research, where participant observations and preliminary notes were initially made. Preliminarily, a hypothetical-deductive procedure was carried out based on ethnographic and monographic methods, where records were produced, identification of categories in the field, unstructured interviews and, finally, the textual production itself. The possibility of the existence of this research is constituted from the perception of the orisha Eshu, Yoruba deity linked to exchanges and communication, and from how its epistemologies reveal the potency, richness and dynamics of the religiosities of African presence within the markets. This research concludes, through the theoreticalmethodological instruments of the Sciences of Religion and its interdisciplinary possibilities, that the market is a special locus of protection and survival of Afro-Brazilian traditions, helping to preserve rites and memory through the fight against the disenchantment of the world, because in the market of Aracaju-SE, enchantment reveals itself as a possibility for Afro-Brazilian religions to preserve their traditions and fight against the daily violence of the accumulative logic of consumption and religious racism, a colonial heritage that until today threatens the afro-religious peoples with the annulment of their bodies and the silencing of their ancestral voices.